Isolamento, biologia e caracterização molecular de bacteriófagos para o manejo da murcha-bacteriana do tomateiro - Carrion, Yanira Lizzeth Limon (2022)
Bacterial wilt is a plant disease caused by bacteria strains of at least three species of Ralstonia belonging to a heterogeneous taxonomic group known as Ralstonia solanacearum species complex (RSSC). It is one of the most important bacterial plant disease that occurs in several crops of agronomic importance such as tomato, potato, banana, pepper, tobacco, eucalyptus, among others. The etiological agents of RSSC are excellent inhabitants of the soil, which aggravates the inefficiency of management, as they survive for long periods in the absence of the host plant. Another critical factor for management is the wide genetic diversity of the RSSC strains and wide range of hosts, the old hierarchical classification divides the RSSC into four phylogenetic groups that have high correlation with the geographic origin, indicated as: Phylotype I – Asia; Phylotype IIA/IIB – Americas; Phylotype III – Africa and Phylotype IV – Indonesia. Currently the four phylotypes have been elevated to the category of species. In Brazil, there are no antibiotics or any agrochemical registered for the control of RSSC strains present in the Americas (Ralstonia solanacearum (Phylotype II) and R. pseudosolanacearum (Phylotype I)), and the control of this disease is carried out through integrated management, which includes actions to avoid injuries caused by implements. agricultural, nematodes and insects, elimination of weeds and crops with bacterial wilt symptoms, crop rotation among other cultural treatments, however, wilt management is not effective. Research carried out in both Asia and America indicates the potential of natural enemies of bacteria, known as bacteriophages (beneficial viruses capable of infecting pathogenic bacteria), for the control of phytobacteria. Thus, the objective of the present research was to investigate an ecological alternative based on phage therapy (use of bacteriophages to manage bacterial plant disease) for the management of RSSC strains and to strengthen the few strategies to circumvent the effects of bacterial wilt. Specifically, the current research was based on the prospection and characterization of lytic bacteriophages capable of infecting the species R. solanacearum and R. pseudosolanacearum in Espírito Santo. Soil, water and plant collections in municipalities of the Brazilian states, including some in Espírito Santo, were carried out to observe the bacteriolytic activity associated with the virus and/or the presence of Ralstonia spp. in cultivation areas with host plants, non-hosts of RSSC strains, in addition to areas of forest fragments. At the same time, isolates of RSSC were collected to be used as bait hosts in viral bioprospecting. After detection of lytic activity, eight bacteriophages (Phage Canuta, Phage Elisiario, Phage Laurinda, Phage Ortiz, Phage Zilma, Phage Kapixawa, Phage Krenak and Phage Zacimba) were isolated and characterized using biological and molecular approaches. Ralstonia sp. collected were molecularly characterized and preserved for host range testing. The host range test with a panel of RSSC strains worldwide showed that bacteriophages infect both R. solanacearum and R. pseudosolanacearum, but are more aggressive when inoculated into isolates of R. solanacearum from Brazil and more specifically the strains from Espírito Santo, where they come from. As for the aggressiveness assessed by the lytic magnitude during the exponential growth phase of R. solanacearum RsB70-PC, the bacteriophages were classified into three groups (Low, Moderate and High Aggressiveness). The analysis of the complete genomes of at least seven of the bacteriophages revealed that they deal with viral isolates of a new species to be cataloged and the phylogenetic reconstruction allowed us to infer that the seven bacteriophages isolated in Espírito Santo are closely related to the taxa of the genus Bakolyvirus (Family Myoviridae). Based on the results, it can be concluded that bacteriophages have an interesting profile of lytic activity against isolates of Ralstonia spp. with potential to be explored biotechnologically to expand the portfolio of ecological perspectives for integrated management of bacterial wilt in the field. Future analyzes of more detailed genomic characterization will be conducted and will gather the necessary elements to enable the application of these biological control agents or their derivatives.